THE ROLE AND FEATURES OF BANKS'ACTIVITIES IN THE SECURITIES MARKET - Krykhovetska , Z.М. (The actual problems of regional economy development, 2021)
The purpose of the investigation is to study the domestic experience of banks in the securities market and outline ways of increasing of the role of the banking system in the functioning of the market, taking into account current conditions in Ukraine. The comparison method is used for comparison quantitative indicators for different periods of time. Economic analysis is used to systematically and comprehensively measure the impact of factors on the activities of banks in the securities market. In the process of using deduction knowledge about processes and phenomena during the transition from general to individual judgments is formed. The classification method is used to distinguish banks' investments in securities by various characteristics. Mathematical statistics are used to quantify phenomena and processes. The article analyzes the issue operations of banks. Peculiarities of banks' issue of shares are investigated. The dynamics and structure of securities other than shares issued by banks are analyzed. A comparative description of the issuance of saving and deposit certificates of banks. Reserves and conditions for growth of banks' issuance operations is determined. The role of investment operations of banks is determined. The structure of investments in securities in the total assets of banks is analyzed. The dynamics of securities, except for shares, in banks' portfolios, the structure of banks' investments in equity instruments is studied. Features of investment strategy in the conditions of economic and political instability in the state are characterized. Peculiarities of banks' professional activity in the securities market are determined. The innovations of the legislation in this direction and opportunities for banks are described. The role of banks as traders in securities in relation to concluded and executed transactions in various securities on the exchange and over-the-counter markets is analyzed. The role of banks in the market of depository services, asset management of private pension funds and clearing is established. It is proposed that banks conduct operations with derivative securities. Ways to intensify investment and professional activities of banks in the securities market are identified.